1999
DOI: 10.1007/978-0-387-35566-5_6
|View full text |Cite
|
Sign up to set email alerts
|

Research and Ethical Issues Arising from Ethnographic Interviews of Patients’ Reactions to an Intelligent Interactive Telephone Health Behavior Advisor

Abstract: People develop strong reactions to machines. Among those reactions are personal relationships that people form with technological objects. Exploration ofways in which individuals relate to information technologies and how individuals see these technologies as being machine-like or being human-like is a fascinating and useful research area. This paper presents a study where these issues arose as a key, although unanticipated, theme in ethnographic interviews conducted among individuals using an intelligent inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…For example, qualitative evaluations have shown that in some programs users anthropomorphize TLC applications although they are fully aware that TLC is only a computer [48][49][50]. The experience of anthropormorphization is enhanced by the use of a recorded human voice rather than a computerized voice.…”
Section: Treating Impulsivitymentioning
confidence: 94%
“…For example, qualitative evaluations have shown that in some programs users anthropomorphize TLC applications although they are fully aware that TLC is only a computer [48][49][50]. The experience of anthropormorphization is enhanced by the use of a recorded human voice rather than a computerized voice.…”
Section: Treating Impulsivitymentioning
confidence: 94%
“…Imaging technologies, among others, have provoked discussion of how the meaning of clinical findings is negotiated among clinicians, and of the effects of making visible clinical work and procedures that previously had been seen only by those involved [109,110,111]. Another new use of technology, telephone keypads which patients/consumers use for input into a voice-response intelligent consultation system [112], like some older applications [29,61,70,113,114], raises issues of the different meanings information and communication technologies have for different users, even among those who appear to be of the same group. Additionally, telehealth involves ethical questions not traditionally considered in evaluation -such as empowerment, effect on home-care and home-care givers, equity and equality of services, how health care roles change, medicalization of social phenomena, and individuals' relationships both with practitioners and technologies -suggesting that such concerns should be reflected in evaluations of other areas of information technology in health care as well [105,112].…”
Section: Current Studiesmentioning
confidence: 99%
“…Another new use of technology, telephone keypads which patients/consumers use for input into a voice-response intelligent consultation system [112], like some older applications [29,61,70,113,114], raises issues of the different meanings information and communication technologies have for different users, even among those who appear to be of the same group. Additionally, telehealth involves ethical questions not traditionally considered in evaluation -such as empowerment, effect on home-care and home-care givers, equity and equality of services, how health care roles change, medicalization of social phenomena, and individuals' relationships both with practitioners and technologies -suggesting that such concerns should be reflected in evaluations of other areas of information technology in health care as well [105,112]. Lastly, evaluation studies themselves may need to change from a focus on individual technologies, individual institutions, and individual users, to the changing context of patientcentered care and integrated delivery systems, and networked technologies that support them [67].…”
Section: Current Studiesmentioning
confidence: 99%
“…Such trials can be very helpful in realizing the promise of automated voice mail technology. Telephone messages from a member of health care delivery team have proven successful in changing health related behaviors such as observing healthier diet and exercise (36), increasing attendance at scheduled appointments for mental health services (37), and increasing immunizations among children (38,52), improving compliance with a course of therapy (39,40), getting regular health screenings done, and taking other preventive health maintenance steps (41)(42)(43). In a randomized clinical trial of 703 adolescents scheduled for routine appointments at an ambulatory pediatric adolescent clinic, those in the intervention group received a single telephone call reminder the day before the appointment.…”
Section: Evidence From Nonautomated Personal Phone Call Studiesmentioning
confidence: 99%
“…Feelings of self-efficacy can come from forming personal relationships with a system. An interactive conversational system TLC HealthCall called weekly for six months 274 sedentary individuals with unhealthy eating habits (36). One week after the system stopped calling, interviews were conducted to find out personal reactions to the system calls.…”
Section: Significance Of Automating Educationmentioning
confidence: 99%